Penilaian Pembimbing Sebagai Media Penginputan Nilai Mahasiswa Sidang Pada PESSTA+ di Perguruan Tinggi - Sudaryono, Sudaryono; Handayani, Indri; Nurmalasari, Yanti (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2018)
ABSTRACT System development is an effort to improve the quality of the system to be more innovative. Raharja College is one of the computer science colleges which has many systems in supporting its academic activities. At Raharja College there is a PESSTA + system (Thesis and Final Assignment Plus Assessment) which provides convenience for students as a medium to fulfill the Thesis trial assessment points. The Advisory Rating is very important to facilitate the lecturer in giving assessments to the mentors aimed at students. However, the current supervisory assessment system has problems that are still using a local network that can only be accessed while on campus. From this problem, it is necessary to develop the appraisal assessment so that it can be accessed in the PESSTA + system so that it becomes more systematic, organized, accessible anywhere online. In developing this assessment system, the supervisor uses swot analysis and elicitation methods. And use one of the PHP Framework, Yii Framework. Keywords: Value input, PESSTA + (Thesis and Final Assignment Plus Assessment), TA / Thesis